Theoretical and experimental study of the drying of whole banana in oven (Research, Society and Development, 2020)
Fresh bananas are fruits with high moisture content after harvest, and are subjected to the drying process to minimize waste and deterioration, and increase shelf life. This work presents a study of drying bananas in an oven. The whole bananas were manually peeled and dried at temperatures of 50 and 60ºC. Lumped models of heat and mass transfer and volume variations of the banana were proposed and fitted to experimental data showing good agreement. The results revealed that the drying-air temperature and the area / volume ratio significantly affect the drying, heating and shrinkage of the banana.